ANÁLISE DA INFLÛENCIA DO COMPLEXO BROCA-PODRIDÃO NO ESTÁGIO INICIAL DA CANA-DE-AÇÚCAR - LUCIANA MARINHO DA SILVA, HELOÍSA (2024)
In Brazilian agribusiness, the cultivation of sugar cane stands out due to its significant production and records of success in sugar exports. Therefore, Brazil has the largest production and export of sugar in the world, accounting for more than 30% in recent years. Therefore, the use of strategic measures and solutions that interfere with factors reducing the productivity of sugarcane fields are extremely important for that the country maintains its position as the world's largest producer of sugar cane. Therefore, for the implementation of sugarcane plantations, some factors must be considered, such as: soil preparation, the choice of a variety that adapts to the production environment, the depth of planting, the time in which planting will be done, the coverage of culms in the furrow, bud distribution, as well as the health of the seedlings. Therefore, this work aimed to evaluate the effects of the borer-rot complex on the sprouting of the RB 92579 and RB 041443 sugarcane varieties grown in Paraíba. The work was conducted at the Regional Development Technology Center, at the Federal University of Paraíba, located in the municipality of João Pessoa. The experiment was in a completely randomized design, with 4 treatments (RB 92579 healthy, RB 92579 brocade, RB 041443 healthy and RB 041443 brocade) and 10 replications. The average sprouting time was evaluated, as well as during periods of 14, 28, 42, 56 and 70 days, as well as assessments of stem height, thickness and number of leaves. Subsequently, the fresh and dry weight of the aerial part and roots and root length were evaluated. The varieties RB 92579 and RB 041443, with symptoms of the borer-rot complex, showed a difference in sprouting time, with the RB 92579 variety being earlier; the borer-rot complex did not cause a difference in plant height and stem thickness of varieties RB 92579 and RB 041443; the borer-rot complex initially affected, up to 14 days, the number of leaves of infected plants compared to healthy plants of the varieties RB 92579 and RB 041443. Healthy and brocaded plants (T2 and T4) of the varieties RB 92579 and RB 041443, respectively infected by the borer-rot complex had the length and dry weight of the lower roots.